EMPIRICAL STUDY OF STUNTING PREVENTION PROGRAM IMPLEMENTATION IN SEI TAROLAT VILLAGE, BILAH HILIR SUB-DISTRICT, LABUHAN BATU DISTRICT: STUDI EMPIRIS PELAKSANAAN PROGRAM PENCEGAHAN STUNTING DI DESA SEI TAROLAT KECAMATAN BILAH HILIR KABUPATEN LABUHAN BATU - Rini Agustini; Rahmadani Yusran (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
This study aims to empirically analyze the stunting prevention and control program in the Sei Tarolat village of Bilah HIlir District, Labuhan Batu Regency. The author in this study used a type of qualitative research that uses a descriptive method. The research location was carried out in the Sei Tarolat village, Bilah HIlir District, Labuhan Batu Regency, at the health office, village office, and puskesmas. Data collection techniques are performed by interview methods and documentation studies. This study found a stunting prevention program not yet done as it should. This is distinguished because of several factors namely limited findings, lack of supervision of the program and inadequate facilities. Still lacking the implementation of the activity of the prevention and prevention program. The results in the difficulty of achieving policy goals in increasing knowledge.